Re-examining cognitive tools: New developments, new perspectives, and new opportunities for educational technology research - Drew, Christopher (Australasian Journal of Educational Technology, 2019)
The concept of educational technologies as cognitive tools or mindtools emphasises the importance of learning with not from technology. When cognitive tools are designed with student-led learning in mind, they ideally help to extend and scaffold learners’ higher-order cognition both when the technology is in use and long after the cognitive partnership has ended. With new wearable, immersive and increasingly personalised educational technologies emerging, this collection of papers reflects upon the value and applicability of the cognitive tools concept in 2019. It works to progress unsettled debates on the definition, design and use of the cognitive tools in light of technological change and highlights the continued relevance of the concept moving forward.